2005
DOI: 10.7202/705504ar
|View full text |Cite
|
Sign up to set email alerts
|

Vitesses de réaction de dissolution et précipitation au voisinage de l'interface oxydo-réducteur dans un lac méromictique : le lac Pavin (Puy de Dôme, France)

Abstract: Une étude à l'échelle centimétrique de l'interface redox situé à la limite entre mixolimnion et monimolimnion d'un lac méromictique (le lac Pavin) a permis d'observer très finement l'évolution de la concentration d'un certain nombre d'éléments chimiques. Nous avons choisi de présenter ici des résultats concernant 5 éléments qui présentent des comportements très contrastés : le rubidium, le fer, le baryum, le vanadium et le manganèse. La comparaison avec un élément conservatif, le sodium, montre que Rb est cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…Stimulation of potential anaerobic CH 4 oxidation by Mn oxides in anoxic sediments from Lake Mendota has been reported previously (Zehnder and Brock, 1980). Miura et al (1992) suggested that, in subsoils, CH 4 contributed to a significant proportion of Fe(III) reduction. Kumaraswamy et al (2001) have shown a stimulation of CH 4 oxidation under anaerobic conditions when Fe(III) was added to anoxic rice soil samples.…”
Section: Anaerobic Pathways Of Methane Oxidationsupporting
confidence: 53%
See 1 more Smart Citation
“…Stimulation of potential anaerobic CH 4 oxidation by Mn oxides in anoxic sediments from Lake Mendota has been reported previously (Zehnder and Brock, 1980). Miura et al (1992) suggested that, in subsoils, CH 4 contributed to a significant proportion of Fe(III) reduction. Kumaraswamy et al (2001) have shown a stimulation of CH 4 oxidation under anaerobic conditions when Fe(III) was added to anoxic rice soil samples.…”
Section: Anaerobic Pathways Of Methane Oxidationsupporting
confidence: 53%
“…Methane concentrations increase sharply at approximately 55 m depth to reach 4 × 10 −3 mol L −1 at 92 m depth. Differences in CH 4 concentrations for the deepest layers are observed in June 2007 but globally from 30 years of observations, the monimolimnion is considered to have reached interannual steady state ( [Viollier et al, 1997] and [Michard et al, 2003] ). However, significant increase of CH 4 is also observed in the epilimnion (Fig.…”
Section: Limnologymentioning
confidence: 99%
“…All parameters taken together, the profiles showed typical trends usually observed in Lake Pavin, i.e. O 2 depletion (detection limit <1 μM) and a sharp increase in C25 and CH 4 at around 60 m depth (Viollier et al , 1997; Michard et al , 2003). In July 2007, the maximum gradients for DO and C25 were located at 57 m depth (oxycline) and 62.1 m depth (mesolimnion), respectively.…”
Section: Resultsmentioning
confidence: 81%
“…It is divided into two permanent stratified layers (Fig. 1) (see Michard et al , 2003). The surface stratum, or mixolimnion, includes three different layers according to variations in depth, temperature, pH and dissolved O 2 (the epilimnion, up to 5–15 m depth, the metalimnion, from the bottom of epilimnion up to 20 m depth and the hypolimnion from approximately 20 to 61 m depth).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation